Soil chemical attributes variability under tillage and no-tillage in a long-term experiment in southern Brazil - Katiaíres Evangelista Delpin Malvezi; Luiz Antônio Zanão Júnior; Ednaldo Carvalho Guimarães; Sidney Rosa Vieira; Natália Pereira (Bioscience Journal, 2018)
Spatial variability of chemical attributes in soils tends to increase under the no-tillage system. However, data regarding this variability under this system for a long time are scarce. This study aimed to evaluate the spatial variability of phosphorus (P), organic matter (OM), pH, aluminum (Al), calcium (Ca), magnesium (Mg), potassium (K), base saturation (V%), sulfur (SO42-), and micronutrients: boron (B), iron (Fe), copper (Cu), manganese (Mn), and zinc (Zn) in soil with conventional tillage and no-tillage treatments for more than three decades in order to optimize fertilization and maintain soil conservation. Samples of Rhodic Hapludox were collected at 0.00–0.20 m depth. Sampling points were spaced 5 m apart, totaling 100 points. All sampling points were georeferenced according to the tillage system. Samples were analyzed chemically. Semivariograms and kriging were used in descriptive statistics and geostatistics analyses of the results. Only micronutrients and P presented distinct spatial variability between the treatments. Most of the analyzed chemical attributes presented spatial dependency in both tillage systems, which may help determine the best form of sampling and indicate adequate fertilization. According to semivariogram range values of OM, Mg, and K, the same sampling strategy may be adopted for analysis in both tillage systems, yet for Al, Ca, and pH the strategy should be specific.